Tracking the future of the ocean from perspective present and past history - Ismail Ali; Mosli Tarsat; Douglas Nyenging Taong (ASIAN SCHOLARS NETWORK, 2024)
This article aims to discuss the future history of the ocean from a past and present perspective, focusing on how historical patterns and current data can be used to predict future challenges and opportunities that marine ecosystems and coastal communities may face. Key questions explored in this study include the impact of climate change on marine biodiversity, the threat of plastic pollution, potential geopolitical conflicts in strategic sea lanes, as well as implications for maritime economics and food security. In terms of conceptual framework studies, this paper uses continuity theory and future uncertainty theory used to analyze the relationship between past changes, current conditions, and future potential in maritime ecosystems. In terms of methodology, the study will use qualitative methods through the analysis of marine history literature and maritime science, as well as the use of simulation methods and predictive models to study future trends. This article also applies maritime climate change theory, maritime geopolitical theory, and maritime economic sustainability theory to support discussions and predict possible future scenarios. The results of this study show that the future history of the ocean depends not only on scientific data but also on the understanding of historical and social contexts, which can help shape a more comprehensive and sustainable ocean management strategy.